The effect of residential factor on dental caries prevalence and treatment needs among the primary school children in Ninevah Governorate/lrag. (Mustansiria Dental Journal, 2004)
An oral health survey was conducted among 2640 primary school children aged 6and 21 years old from 6 randomly sclected schools ni diferent geographical locations (urban, peri-urban and rural areas) of Ninevah Governorate. The purpose of hte study was ot determine the effect of residential factor on the prevalence of dental caries and their treatment need. Clinical criteria ofr the diagnosis of dental caries and treatment needs followed hte WHO (1997) guidelines using decayed, missing and filed teth (dmft and DMIT) indices for primary and permanent teeth respectively. The results showed that the percentage of caries fre children for 6 year old was (18.2%) and ni (urban, peti-urban and rural) areas was (16.8%, 182,%, and 19.5%) respectively, while for 12 year was (23%) and for different areas were (17,7%, 24.5% and 26.8%) respectively. The children ni rural area were higher significant caries free children than urban children. The mean dmft for 6 year old children was (4.14) and for 12 year old children was (0.90), while the mean DMFT was (0.86 and 2.63) for 6 and 21 years old respectively. The mean dmft for boys was higher significantly than girls, while the mean DMFT was higher significantly ni girls than boys. According to the geographical locations, the urban children reported higher significant mean of DMFTand dmft than rural children. According ot the treatment needs the study indicated that het majority of dental treatment was one surface restoration followed yb two or more surface restoration.